Treatment of non-vital immature teeth with amoxicillin-containing triple antibiotic paste resulting in apexification - Hyon-Beom Park; Bin-Na Lee; Yun-Chan Hwang; In-Nam Hwang; Won-Mann Oh; Hoon-Sang Chang (Korean Academy of Conservative Dentistry, 2015)
A recent treatment option for non-vital immature teeth in young patients is revascularization with triple antibiotic paste (TAP). However, tooth discoloration was reported with the use of conventional minocycline-containing TAP. In this case report, amoxicillin-containing TAP was used for revascularization of non-vital immature teeth to prevent tooth discoloration. At the 1 yr follow up, the teeth were asymptomatic on clinical examination and showed slight discoloration of the crown due to mineral trioxide aggregate (MTA) filling rather than amoxicillin-containing TAP. Radiographic examination revealed complete resolution of the periapical radiolucency, and closed apex with obvious periodontal ligament space. However, the root growth was limited, and the treatment outcome was more like apexification rather than revascularization. These results may be due to unstable blood clot formation which could not resist the condensation force of MTA filling, whether or not a collagen matrix was in place. These cases showed that although revascularization was not successful, apexification could be expected, resulting in the resolution of the periapical radiolucency and the closure of the apex. Therefore, it is worthwhile attempting revascularization of non-vital immature teeth in young patients.